Applications of TiO2/Jackfruit peel nanocomposites in solar still: Experimental analysis and performance evaluation. (October 2022) - Alsaiari, Abdulmohsen O.; Shanmugan, S.; Abulkhair, Hani; Bamasag, Ahmad; Moustafa, Essam B.; Alsulami, Radi A.; Ahmad, Iqbal; Elsheikh, Ammar
Abstract: An effort has been made to synthesize nanocomposites of TiO2 /jackfruit peel via green synthesis. Various concentration of the synthesized nanocomposite (0.1%, 0.2% and 0.3%) has been combined with mat black paint to coat the sides and base of the proposed single slope single basin solar still (PSBSS). The structural and morphological properties of synthesized nanocomposite (JPT) were characterized using XRD and SEM. It was observed that the nanocomposite of JPT has a porous structure with 85% crystallinity with grain size ranging from 40 to 60 nm. The nanocomposite is mixed with cobalt (II) chloride (CoCl2 ), thiourea (CH4 N2 S) and silicon dioxide (SiO2 ) to make a new hybrid nanofluid (CTS) with a ratio of 10%, 20%, 30%, 40%, 50% and 60%. Silver-color steel balls filled with CTS was placed in the basin of the PSBSS at equal intervals to enhance the heat transfer process inside the still. The PSBSS with nanocomposites (0.3%), nanofluids (40%) fill the silver-color steel balls (JPTCTSS) has high productivity of 8.7919 L/m 2 day, which is 50.55% higher than that of the conventional solar still (CSS) with nanofluid along with the saline water in the basin.